Textile-based flexible linear-to-circular polarizing surface for s-band pico-satellites - Hidayath Mirza; Ping Jack Soh; Azremi Abdullah Al-Hadi; Toufiq Md Hossain; Rais Ahmad Sheikh; Mohd Faizal Jamlos (Institute of Advanced Engineering and Science, 2019)
This paper presents a single layered textile-based flexible linear-to-circular polarizing surface. The proposed structure is designed based on a rectangular ring structure for CubeSat application in the S-band. Each unit cell is sized at 0.35λ×0.33λ×0.2λ for operation centered at 2.2 GHz. This unit cell is then multiplied into a 9x10 array to form the polarizing surface. It features a 3 dB axial ratio bandwidth (ARBW) of 34.73%, with a minimum AR of 0.28 dB. Besides that, it also offers a 90 % conversion efficiency bandwidth of up to 47.34%. The proposed structure’s performance is validated by placing it in front of a patch antenna operating at 2.2 GHz. The antenna performance indicated an increase in terms of gain from 3.14 dBi to 7.33 dBi when integrated with the polarizing surface, besides successfully converting linearly-polarized waves to circularly-polarized.